2010
DOI: 10.1371/journal.pone.0011273
|View full text |Cite
|
Sign up to set email alerts
|

Open Access to the Scientific Journal Literature: Situation 2009

Abstract: BackgroundThe Internet has recently made possible the free global availability of scientific journal articles. Open Access (OA) can occur either via OA scientific journals, or via authors posting manuscripts of articles published in subscription journals in open web repositories. So far there have been few systematic studies showing how big the extent of OA is, in particular studies covering all fields of science.Methodology/Principal FindingsThe proportion of peer reviewed scholarly journal articles, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
318
4
37

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 386 publications
(388 citation statements)
references
References 16 publications
9
318
4
37
Order By: Relevance
“…Many studies have estimated what proportion of the literature is available OA, including Björk et al (2010), Laakso et al (2011), Laakso andBjörk (2012), Gargouri, Lariviere, Gingras, Carr, and Harnad (2012), Archambault (2013), Archambault et al (2014), andChen (2014). We are not aware of any studies since 2014.…”
Section: Prevalence Of Oamentioning
confidence: 99%
“…Many studies have estimated what proportion of the literature is available OA, including Björk et al (2010), Laakso et al (2011), Laakso andBjörk (2012), Gargouri, Lariviere, Gingras, Carr, and Harnad (2012), Archambault (2013), Archambault et al (2014), andChen (2014). We are not aware of any studies since 2014.…”
Section: Prevalence Of Oamentioning
confidence: 99%
“…PubMed Central (PMC) fills this role for life sciences journals; when studying OA scientific literature Björk et al (2010) found PMC to be the most frequently encountered subject based repository, along with arXiv. Standards for inclusion in a repository vary.…”
Section: Observedmentioning
confidence: 99%
“…The lowest overall OA share is in chemistry with 13 % and the highest in earth sciences with 33 %.'' (Björk et al 2010). …”
Section: Green or Gold: Which Is The Better Way?mentioning
confidence: 99%